Principles of Sociological Inquiry Qualitative and Quantitative Methods - Blackstone, Amy (Open textbook library., 2012)
The author of Principles of Sociological Inquiry: Qualitative and Quantitative Methods, Amy Blackstone, started envisioning this textbook while sitting in her own undergraduate sociology research methods class. She enjoyed the material but wondered about its relevance to her everyday life and future plans (the idea that one day she would be teaching such a class hadn't yet occurred to her). Now that she teaches the research methods course, she realizes that students today wonder the very same thing. While the importance of understanding research methods is usually clear to those students who intend to pursue an advanced degree, Amy wanted to write a text that would assist research methods teachers in demonstrating to all types of students the relevance of this course. In addition, Amy Blackstone's experience as an active researcher who uses both qualitative and quantitative methods made her acutely aware of the need for a balanced approach in teaching methods of sociological inquiry. Together, Amy Blackstone's experiences as a student, researcher, and teacher shape the three overriding objectives of Principles of Sociological Inquiry: Qualitative and Quantitative Methods: Relevance, Balance, and Accessibility. Principles of Sociological Inquiry: Qualitative and Quantitative Methods emphasizes the relevance of research methods for the everyday lives of its readers, undergraduate students.Each chapter describes how research methodology is useful for students in the multiple roles they fill: As consumers of popular and public information As citizens As current and future employees. Connections to these roles are made throughout and directly within the main text of the book Principles of Sociological Inquiry: Qualitative and Quantitative Methods also provides balanced coverage of qualitative and quantitative approaches by integrating a variety of examples from recent and classic sociological research. The text challenges students to debate and discuss the strengths and weaknesses of both approaches. Finally, one of the most important goals Amy had for Principles of Sociological Inquiry: Qualitative and Quantitative Methods was to introduce students to the core principles of social research in a way that is straightforward and engaging. As such, the text reflects public sociology's emphasis on making sociology accessible and readable. No one can validate that claim more than a teacher or student. So, take a look for yourself today and review Principles of Sociological Inquiry: Qualitative and Quantitative Methods by Amy Blackstone to see if its approach toward relevance, balance, and accessibility are right for your course and students.